2017
DOI: 10.1111/ppa.12803
|View full text |Cite
|
Sign up to set email alerts
|

A new genus and species for the globally important, multihost root pathogen Thielaviopsis basicola

Abstract: The plant pathogenic asexual fungus Thielaviopsis basicola (Ascomycota) causes black root rot on many important agricultural and ornamental plant species. Since its first description in 1850, this species has had a tumultuous taxonomic history, being classified in many different genera. Thus far, DNA‐based techniques have not played a significant role in identification of T. basicola and have been used only to confirm its placement in the Microascales. This investigation reconsidered the phylogenetic placement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 34 publications
(66 reference statements)
1
51
0
Order By: Relevance
“…Huntiella species are members of the family Ceratocystidaceae (Microascales, Sordariomycetes) as defined by De Beer et al (2014). This family includes 15 genera, namely Ambrosiella, Berkeleyomyces, Bretziella, Catunica, Ceratocystis, Chalaropsis, Davidsoniella, Endoconidiophora, Huntiella, Meredithiella, Phialophoropsis, Solaloca, Tielaviopsis, Toshiolenlla andWolfgangiella (De Beer et al 2014, 2017;Mayers et al 2015Mayers et al , 2020Nel et al 2018). The type species of Huntiella, H. moniliformis, was first isolated from a sweetgum (Liquidambar styraciflua) in Texas, USA (Von Schrenk 1903).…”
Section: Introductionmentioning
confidence: 99%
“…Huntiella species are members of the family Ceratocystidaceae (Microascales, Sordariomycetes) as defined by De Beer et al (2014). This family includes 15 genera, namely Ambrosiella, Berkeleyomyces, Bretziella, Catunica, Ceratocystis, Chalaropsis, Davidsoniella, Endoconidiophora, Huntiella, Meredithiella, Phialophoropsis, Solaloca, Tielaviopsis, Toshiolenlla andWolfgangiella (De Beer et al 2014, 2017;Mayers et al 2015Mayers et al , 2020Nel et al 2018). The type species of Huntiella, H. moniliformis, was first isolated from a sweetgum (Liquidambar styraciflua) in Texas, USA (Von Schrenk 1903).…”
Section: Introductionmentioning
confidence: 99%
“…However, these morphological and biological traits have evolved more than once in the Ascomycota and phylogenetic analyses have shown that these fungi reside in two different orders, the Ophiostomatales and Microascales ( De Beer et al 2013 ). The Ophiostomatales currently accommodates a single family, the Ophiostomataceae , that includes ten genera ( Bateman et al 2017 , De Beer et al 2016a , De Beer et al 2016b , Van der Linde et al 2016 ), while the Microascales comprises of five families, of which the Ceratocystidaceae , Gondwanamycetaceae and Graphiaceae include 14 genera of ophiostomatoid fungi ( De Beer et al 2014 , 2017 , Mayers et al 2015 , Nel et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both C. adiposa and C. norvegica are clearly placed outside of Ceratocystis s.str. but are not accommodated by any currently-defined genera ( De Beer et al 2014 , 2017 , Mayers et al 2015 , Nel et al 2017 ). Both of these species (and B. fagacearum ) have no known close relatives, and they are biologically and morphologically distinct from each other and the ambrosia beetle symbionts.…”
Section: Resultsmentioning
confidence: 99%
“…Accession numbers for newly-generated sequences and those from previous studies ( De Beer et al 2014 , Mayers et al 2015 , 2017 , 2018 , Lin et al 2017 ) are listed in Table S2 . Representatives of all major lineages in the Ceratocystidaceae were included ( De Beer et al 2014 , 2017 , Nel et al 2017 ), but a close relative of the family, Cornuvesica ( Marincowitz et al 2015 ), was not included in analyses due to inadequate sequence data. Sequences also included those of a Michigan isolate of an unnamed Microascales sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation